Teachers’ and teacher trainees’ reading strategy use and reading habits in their mother tongue and foreign language (Training and Practice : Journal of Educational Sciences, 2021)
Teachers have an important effect on their students thus it is essential to examine this rather neglected area of research. Our aim is to identify Hungarian teachers’ (N=256) and teacher trainees’ (N=70) reading strategy use and reading habits in mother tongue and foreign language. The items of the Hungarian version of MARSI (Metacognitive Awareness of Reading Strategies) were adapted (Molitorisz, 2013), along with items on reading habits. Based on the results those in the sample use fewer reading strategies and read less in foreign languages. Mostly short texts and global reading strategies are preferred both in mother tongue and foreign language. This research is a step towards shedding a light on Hungarian teachers’ reading.